Water wave diffraction by a circular barrier in two superposed fluids with an ice-cover. (1st July 2020) - Islam, Najnin; Gayen, R.
Abstract: Water wave interaction with a circular barrier placed in the lower fluid of a medium comprised of two superposed fluids is investigated. The topmost surface of this medium is covered by a thin sheet of ice. The existence of two different incident waves along the ice-covered surface and the interface gives rise to two different problems. Both the problems are tackled by transforming them into hypersingular integral equations for the jump in the potential across the circular barrier. The integral equations are solved numerically and the solutions are used to find relevant physical quantities. The qualitative features of these quantities are graphically analyzed by varying the arc length of the barrier, the depth of their submergence, the ice-parameters and the depth ratio of the fluids. The present results are compared successfully with previous results for a curved barrier present in a single layer fluid. Highlights: Water wave scattering by a circular-arc-shaped plate placed in a two-layer ice-covered fluid is studied in two-dimensions. Hypersingular integral equation method is applied to solve the problem. The reflection and the transmission coefficients and the hydrodynamic force for surface and internal modes are computed. The effects of varying parametric values on the relevant physical quantities are presented graphically. Presented graphs have shown that the circular-arc-shaped plate reduced incident wave energy.